Integrating Self-Paced E-Learning with Conventional Classroom Learning in Nigeria Educational System - Soyemi, J; Ogunyinka, O. I; Soyemi, O. B (Mediterranean Journal of Social Sciences, 2012)
The advances in Information and Communication Technology (ICT) and its rapid growth are changing the way peopleuse, develop, process and disseminate information and instruction {technology}. There is no doubt that ICT use in the classroomincrease student’s motivation to learn, engage in learning and give independence in learning. Evidence shows that there is acorrelation between using ICT in schools and students academic achievement across a range of courses. Student arecomfortable and fulfilled in an ICT environment and using this as a bench mark, [integrating it with a self-paced student centeredlearning] in conjunction with the conventional classroom learning will go a long way to improve learning thereby increasingacademic performance of the students at large. This paper explores the potential of self-paced e-learning alongside withconventional classroom learning and the positive impact the integration of the two can have on student’s academic performancewhen incorporated into the Nigeria Educational system.